Development of a Critical Thinking Skills Test Instrument Based on Rasch Modelling for Temperature and Heat - Elmerita Dwi Agustin; Hera Novia; Raden Giovanni Ariantara (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Critical thinking skills are essential competencies in 21st-century physics learning. However, the availability of assessment instruments that accurately measure these skills remains limited, particularly for physics topics such as temperature and heat. Previous studies have rarely integrated Rasch modelling into the development of critical-thinking assessment instruments, particularly at the secondary school level. Therefore, this study aimed to develop and analyze the validity, reliability, and item fit of a critical thinking skills test instrument on temperature and heat topics using the Rasch model. This study employed a Research and Development (R&D) approach using the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation stages. The instrument consisted of 20 multiple-choice items constructed from critical-thinking indicators. Content validity was analyzed using Aiken’s V, while empirical analysis was conducted using the Rasch model through Ministeps Software. The analysis included item reliability, person reliability, item fit, difficulty level, and unidimensionality. The results showed that the instrument achieved an average Aiken’s V value of 0.8068, indicating that the instrument met the content validity criteria. Rasch analysis revealed that the item reliability was 0.86, while the person reliability was 0.35. In addition, 19 items were categorized as fit, whereas one item was identified as a misfit and required revision. The instrument also met the unidimensionality requirement with a raw variance explained value of 22.7%. In conclusion, the developed instrument meets the criteria for validity, reliability, and item fit and is suitable for measuring students’ critical thinking skills on topics related to temperature and heat. The findings indicate that Rasch modelling can support the development of more objective and comprehensive assessment instruments for physics learning and classroom assessment practices.